2008
DOI: 10.1152/ajpheart.01399.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemic flow heterogeneity within the calf, foot, and forearm measured with continuous arterial spin labeling MRI

Abstract: Arterial spin labeling (ASL) is a noninvasive magnetic resonance imaging (MRI) technique for microvascular blood flow measurement. We used a continuous ASL scheme (CASL) to investigate the hyperemic flow difference between major muscle groups in human extremities. Twenty-four healthy subjects with no evidence of vascular disease were recruited. MRI was conducted on a 3.0 Tesla Siemens Trio whole body system with a transmit/receive knee coil. A nonmagnetic orthopedic tourniquet system was used to create a 5-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
40
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
6
40
2
Order By: Relevance
“…For example, previous studies (8)(9)(10)(11)(12)(13) have reported a higher percentage of type I fibers in the soleus (69-88%) than the gastrocnemius (43-60%) in humans. Consistent with a typical phenotype profile of a muscle composed primarily of type I fibers, the human soleus has been associated with slow neuronal firing rates during contractions (14), long contraction times (15), enhanced microvascular functioning (16,17), and low glycolytic enzyme activity (8). However, succinate dehydrogenase (SDH) activity, an in vitro marker of oxidative potential, was observed to be similar in the lateral gastrocnemius and soleus (11).…”
Section: Introductionmentioning
confidence: 77%
“…For example, previous studies (8)(9)(10)(11)(12)(13) have reported a higher percentage of type I fibers in the soleus (69-88%) than the gastrocnemius (43-60%) in humans. Consistent with a typical phenotype profile of a muscle composed primarily of type I fibers, the human soleus has been associated with slow neuronal firing rates during contractions (14), long contraction times (15), enhanced microvascular functioning (16,17), and low glycolytic enzyme activity (8). However, succinate dehydrogenase (SDH) activity, an in vitro marker of oxidative potential, was observed to be similar in the lateral gastrocnemius and soleus (11).…”
Section: Introductionmentioning
confidence: 77%
“…In skeletal muscle, this can be accomplished by measuring the response during or following exercise (functional hyperemia), 79 or following induced ischemia (reactive hyperemia). 7,10,11 Functional vascular impairment manifests as a blunting and delay of reperfusion in response to the stressor. 1 Even though it is not physiologically analogous to the demands of daily living, reactive hyperemia provides a more reproducible and subject effort-independent stimulus compared to functional hyperemia, and thus has been purported as the preferred stressor for studying peripheral vascular function.…”
mentioning
confidence: 99%
“…This signal can be converted into perfusion in units of mL/min/100g through application of various models. 7,11,15,16 …”
mentioning
confidence: 99%
See 2 more Smart Citations